Study of cardiovascular responses to isometric hand grip test in medical students with hypertensive parents - K. A., Malarvannan; A., Sivapriya (International Journal of Research in Medical Sciences, 2023)
Background: Hypertension is one of the most powerful risk factors for cardiovascular disease. This biggest health challenge has to be detected early so that preventive measures can be taken for the susceptible population. Increased cardiovascular stress responsivity with sustained isometric muscle contraction is associated with cardiovascular disease. So this isometric handgrip exercise is a simple, non-invasive screening test to assess the risk of development of hypertension in future. Aim and objective of the study was to identify the chance of inheritance of hypertension in medical students of hypertensive parents. Methods: After getting ethical committee approval, in this cross sectional study, 50 medical students of Government Sivagangai Medical college with normotensive and hypertensive parents were selected. Heart rate (bpm) and blood pressure (mmHg) before, immediately and 5 minutes after isometric hand grip exercise using hand grip dyanamometer in both the groups. Results: Statistical analysis of the values among the participants was done by student t-test using statistical package for the social sciences (SPSS) version 11.0.and the results were compared between the study and control groups. A ‘p’ value of <0.05 is considered significant. Cardiovascular responses are found to be significantly higher in study group (p<0.001). Conclusions: Early and regular screening of the students with hypertensive parents is necessary to prevent cardiovascular complications in future by emphasizing the life style modifications.